Three new species of sea star parasite Dendrogaster (Crustacea: Thecostraca) from Japan - Saito, Nobuhiro; Moritaki, Takeya; Minakata, Keiji; Wakabayashi, Kaori (Zootaxa, 2024)
Three new species of ascothoracidan crustaceans, Dendrogaster danni sp. nov., Dendrogaster tanabensis sp. nov., and Dendrogaster jinshomaruae sp. nov. are described from the sea around the Kii Peninsula on the Pacific coast of central Japan. They are found in the coelomic cavities of the sea stars, Neoferdina japonica Oguro & Misaki, 1986., Henricia sp., and Coronaster volsellatus (Sladen, 1889), respectively. Morphological examinations and DNA barcoding analyses of these new species are reported in this study. The emergence of Dendrogaster from their host sea stars is also noted. These findings represent the 11th to 13th species of Dendrogaster that infest Japanese sea stars.